Improve The Security of The Vigenère Cypher Algorithm by Modifying the Encoding Table and Key - Agung Purnomo Sidik (International Journal of Basic and Applied Science, 2021)
This investigation was conducted to move forward the security of the vigenère cypher calculation by tending to the key conveyance issue and the most key issue within the calculation if cryptoanalysts effectively got it. The working demonstrates employments a 512-bit Electronic Code Book (ECB). The essential key utilized was a 512-bit arbitrary key. The randomized encoding table was also generated by the Blum Blum Shub calculation employing a scrambler key. The RSA calculation was utilized to scramble 512-bits random keys and scrambler keys. It comes about to appear that the proposed calculation does not include a key dissemination issue. With a randomized encoding table, the 512-bits arbitrary key cannot be utilized to unscramble the ciphertext off chance that cryptanalysis did not know the mixed table utilized. The preparing time appeared the proportion of the contrast of the vigenère cypher calculation. The proposed calculation was not as well essentially distinctive, and the longer the message was handled, the proportion of the time distinction possessed was moreover getting closer to one, which implies the distinction was not critical. The coming about ciphertext was too exceptionally secure, where the coming about ciphertext was irregular since the key utilized was random, and there were 3.75 x 10126 keys combination. This algorithm can be an alternative algorithm that is fast, safe, and easy to implement